If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(X + -1) = 10 + -2(3X + 2) Reorder the terms: 5(-1 + X) = 10 + -2(3X + 2) (-1 * 5 + X * 5) = 10 + -2(3X + 2) (-5 + 5X) = 10 + -2(3X + 2) Reorder the terms: -5 + 5X = 10 + -2(2 + 3X) -5 + 5X = 10 + (2 * -2 + 3X * -2) -5 + 5X = 10 + (-4 + -6X) Combine like terms: 10 + -4 = 6 -5 + 5X = 6 + -6X Solving -5 + 5X = 6 + -6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6X' to each side of the equation. -5 + 5X + 6X = 6 + -6X + 6X Combine like terms: 5X + 6X = 11X -5 + 11X = 6 + -6X + 6X Combine like terms: -6X + 6X = 0 -5 + 11X = 6 + 0 -5 + 11X = 6 Add '5' to each side of the equation. -5 + 5 + 11X = 6 + 5 Combine like terms: -5 + 5 = 0 0 + 11X = 6 + 5 11X = 6 + 5 Combine like terms: 6 + 5 = 11 11X = 11 Divide each side by '11'. X = 1 Simplifying X = 1
| 3x^2-12x(1.5)= | | 5+.5c=14 | | 2(x-5)-x=-6 | | 72-5x=13x+20 | | 6+5n=9-2n | | 0.07x*0.03=0.38 | | 1.4(a+6)=2.8(a+10) | | -97-8x=60-22x | | 112=1.5s | | 6x(2x+7)= | | 9+3(-7y+1)=6(y+7)+6 | | 50+65+x=505 | | 4x-3=7x+18 | | 6x(2x-7)= | | 9x=14x-21 | | -7x+11=19-x | | 3+10n=12n-3 | | 0-5x=6x+19 | | (y/4)=-10 | | g(x)=x^2-2X+5 | | x^3+3sinx+2cosx=2 | | 85-6x=w | | 2-5y=18 | | 3x-7+4=28 | | 2432+42= | | 5x+2+4x=7+2x-4 | | 2432+4= | | 2(3x+2)-4(3x-1)=-4 | | 4x^2-5x+9=7x+4 | | 20w^2-9w=0 | | 3(3x+4)=5(-x+2) | | 4x^2-23x+22=-6x+4 |